The Uncomfortable Lack of Space and Spatiality in Strategy Studies as Social Practice: a Research Agenda - Borges, Jacquelaine Florindo; Takahashi, Adriana Roseli Wünsch (Organizações & Sociedade, 2021)
In this theoretical essay, we analyze how strategy studies, seen as social practice, benefit from a dialogue with studies of Philosophy, Sociology and Geography about space and associated concepts such as spatiality, territory, region and place. These studies compose a diversified epistemic and theoretical framework. Human and Social Sciences have promoted two epistemic changes in the late 20th century, namely: the return to practice and space. The practical turn in the organizational strategy field was not followed by spatial turn. The aims of the present study are to analyze the spatiality of strategy seen as practice and to suggest a research agenda to connect organizational strategy to topics that go beyond the business world. It has also expanded the frontiers of studies focused on investigating strategy as a complex of socially-situated strategizing practices implemented by a plurality of actors who create and transform space as multiplicity: physical / material, cultural / symbolic, political / economic, represented / narrated.